UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG AKAR TUBA (Derris elliptica (Roxb.) Benth) MENGENDALIKAN HAMA PENGHISAP POLONG (RiptortuslinearisF.) PADA TANAMAN KEDELAI (Glycinemax(L.) Meriill) - Putri, Nela Eka; fauzana, Hafiz (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Pod-sucking pest (Riptortus linearis) is the main pests of soybean plant. Safe and environmentally friendly control is the use of botanical insecticides from tuba plant (Derris elliptica). This study aims to obtain the effective concentration of tuba root extract powder (Derriselliptica) to control pod-sucking pests (Riptortus linearis) in soybean plant.This research was conducted at the Plant Pest Laboratory, Faculty of Agriculture, Riau University and Jalan Rajawali Sakti, Panam, Pekanbaru. The research was conducted with an experimental method using a complete randomized design (CRD) consisting of 6 treatments and 4 replications. Concentration treatment of tuba root extract powder given was the concentration of tuba root extract powderof 0 g.l-1 water, 20 g.l-1 water, 40 g.l-1 water, 60 g.l-1 water, 80 g.l-1 water, and 100 g.l-1 water. The parameters observed were the initial time of death, lethal time50, daily mortality, total mortality, and changes in behavior and morphology. The results present that the concentration of 100 g.l-1 water was the most effective concentration with the fastest initial death at 3,75 hours, the fastest LT50 at 47,25 hours, the percentage of daily mortality was 32,5% on the first day after application, and a total mortality of 92,50 % during 90 hours of observation.Â Key words:Derris elliptica, Riptortus linearis, botanical insecticide,Â  concentration.